METHODOLOGY FOR APPLYING MODERN TECHNOLOGIES FOR ASSESSING THE QUALITY OF EDUCATION IN MATH (Web of Teachers: Inderscience Research, 2024)
This article considered about testing, a rating system and educational portfolios, which can be used as innovative tools in assessing the quality of educational results and it is discussed about their pluses and drawbacks.